Pengaruh Motivasi Kerja dan Kompensasi terhadap Turnover Intention SPG PT Arina Multikarya Bandung pada Brand Kino - Rama Novandres, Esa; Aam Rachmat Mulyana (Journal Of Administration and Educational Management (ALIGNMENT), 2025)
This study aims to analyze the influence of work motivation and compensation on turnover intention among Sales Promotion Girls (SPGs) at PT Arina Multikarya Bandung, working with the Kino brand. The research method used was quantitative with a descriptive and associative approach. The population in this study was all 42 SPGs at PT Arina Multikarya Bandung, working with the Kino brand. Data collection techniques included questionnaires, interviews, and documentation. Data analysis used multiple linear regression and a coefficient of determination test using SPSS version 26. The results showed that SPG work motivation was in the high category with a mean value of 3.68, compensation was in the appropriate category with a mean value of 3.84, and turnover intention was in the low category with a mean value of 1.97. Partially, work motivation had a negative effect on turnover intention, and compensation also had a negative effect on turnover intention. Simultaneously, work motivation and compensation had a significant effect on turnover intention with a coefficient of determination of 0.434, meaning that both variables contributed 43.4% and were considered quite strong. The conclusion of this study is that the higher the work motivation and compensation received, the lower the turnover intention rate among sales promotion staff (SPG) at PT Arina Multikarya Bandung for the Kino brand.   Keywords: Work Motivation, Compensation, Turnover Intention, SPG